REDUCING FATIGUE SCORE WITH PHYSICAL EXERCISE IN CHILDREN WITH CANCER - Hermalinda Herman; Dwi Novrianda (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2017)
Physical problems that often arise in children with cancer include fatigue. Fatigue or tiredness is a condition that leads to stress and a deep problem for patients suffering from cancer. Nursing interventions on cancer-related fatigue which quite effective is regular physical exercise. The purpose of this study was to identify the relationship of physical exercise with a score of fatigue in children with cancer. The method used is descriptive analytic with cross sectional study. The study was conducted in Child Care ward of DR. M.Djamil Hospital In May and October 2015. The sample in this study were 30 children with cancer who undergoing chemoteraphy that taken with accidental sampling technique. Data collection was a questionnaire about fatigue scores in children and child physical exercise performed before undergoing chemotherapy. Data were analyzed by independent t test. The mean score of fatigue in children who do physical exercise was 39.86 with a standard deviation of 6.98. In children who do not do physical exercise, the average fatigue score was 46.62 with a standard deviation of 7.60. it can be concluded that there was a significant differences in fatigue scoring between children who did physical exercise and didnt do that ( p value 0.017).In conclusion physical education programs in patients with cancer are hopefully controlled, coordinated and sustainable, and became one of the nursing intervention in patients with cancer who experience fatigue.